2017
DOI: 10.1007/s40830-017-0099-y
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Nanoindentation and Nano-Impact Fatigue Mechanisms of Functionally Graded TiN/TiNi Film

Abstract: The mechanisms of nanoscale fatigue of functionally graded TiN/TiNi films have been studied using multiple-loading cycle nanoindentation and nano-impact tests. The functionally graded films were sputter deposited onto silicon substrates, in which the TiNi film provides pseudo-elasticity and shape memory behaviour, while a top TiN surface layer provides tribological and anti-corrosion properties. Nanomechanical tests were performed to investigate the localised film performance and failure modes of the functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…In classical indentation experiments, only single loading and unloading on the specimen is performed for determining the desired mechanical properties. However, to study the fatigue life in materials, the cyclic indentation has attracted the attention of many authors [ 17 , 18 , 19 , 20 ]. For example, Lyamkin et al [ 17 ] have shown the potential of cyclic indentation for studying the fatigue properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In classical indentation experiments, only single loading and unloading on the specimen is performed for determining the desired mechanical properties. However, to study the fatigue life in materials, the cyclic indentation has attracted the attention of many authors [ 17 , 18 , 19 , 20 ]. For example, Lyamkin et al [ 17 ] have shown the potential of cyclic indentation for studying the fatigue properties.…”
Section: Introductionmentioning
confidence: 99%
“…As the cycles of indentations are repeated at the same location, the elastoplastic area of high cyclic indentation demonstrates fatigue under these conditions. For instance, a nanoimpact fatigue test has been studied by Faisal et al [ 18 ] by using cyclic indentation, and they have concluded that the indenter geometrical shape (Berkovich or conical) and the indentation loading history are crucial in inducing film failure. Moreover, Haghshenas et al [ 19 ] have employed cyclic nanoindentation in order to determine the indentation size effects and the strain rate sensitivity for tantalum.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoindentation has emerged as a suitable techniques to study the deformation behavior of the material in the near-surface region with varying loads and other related parameters [6][7][8][9][10][11][12]. It has been previously used for primarily studying the mechanical properties of HgCdTe alloys by several researchers [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…These studies although explored several useful properties of the HgCdTe films, they were focussed mainly on single cycle nanoindenation and lacked in providing the desired parameters and deformation behaviour during actual lapping and polishing induced cyclic loading/unloading, which could better be studied using cyclic nanoindentation. The cyclic nanoindentation can provide crucial information on the evolution of mechanical properties with repeated loading-unloading of the near surface material [12,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical characterization of materials by means of micro-and nanoindentation in the form of a hardness test or cyclic indentation with different indenter shapes and measurement parameters is a useful and well-established way to estimate important material parameters such as elastic modulus, or, in some cases, even fatigue limit [1][2][3][4]. Furthermore, numerical methods add more detailed information to the experiments concerning the stress-strain behavior [3,5,6]. Molecular dynamics (MD) simulations specifically provided a valuable understanding of the nanoplasticity and dislocation density generated underneath a nanoindenter [7,8].…”
Section: Introductionmentioning
confidence: 99%